(untitled) (Journal of Psychiatrists’ Association of Nepal, 2021)
Introduction: First episode psychosis refers to the first time someone experiences psychotic symptoms or a psychotic episode. There are evidences related to the role of major life events and childhood trauma in the development of first episode psychosis. There are few studies regarding the environmental exposure to stressful life events and how these events might influence the onset of a psychotic disorder, and role of perceived stress. This study aimed to identify the relationship between stressful life events and first episode psychosis in Nepalese context. Material And Method: It was a hospital based cross-sectional, descriptive study. A total of 50 cases of first episode psychosis were included and the diagnosis was made according to ICD 10- Diagnostic Criteria for Research and verified by two consultant psychiatrists. Semi Structured Performa was designed to collect the information about the socio demographic data and perceived stress was assessed with Presumptive Stressful Life Events Scale (PSLES). Results: There were 62% female and 38% male patients with first episode psychosis with mean age 26.32 years. Majority of the participants were from rural areas (94%), married (58%), educated up to primary level (38%) and housewife (40%). 60.7% of ATPD had stressful life events (P =0. 000)which was higher than the stressful life events in patient with Schizophrenia (P =0. 005). There was a positive correlation between stressful life events and gender, setting, socioeconomic status and Diagnosis (P <0.05). Conclusion: Results show the relevance of presence of stressful life events as a potent source of perceived stress in first episode psychosis sample. Therefore this study highlights the importance of psychosocial intervention in this vulnerable group for management of illness and might be an important strategy for prevention.